2017
DOI: 10.1371/journal.pone.0178782
|View full text |Cite
|
Sign up to set email alerts
|

Chronotypes in the US – Influence of age and sex

Abstract: An individual’s chronotype reflects how the circadian system embeds itself into the 24-h day with rhythms in physiology, cognition and behavior occurring accordingly earlier or later. In view of an increasing number of people working at unusual times and linked health and safety risks, the wide range in human chronotypes may provide opportunities to allow people to work (and sleep) at times that are in synch with their circadian physiology. We aimed at estimating the distribution of chronotypes in the US popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
270
4
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(324 citation statements)
references
References 54 publications
40
270
4
10
Order By: Relevance
“…We find a greater discordance to prior work with our cohort’s sleep midpoints, which typically vary from 3:00am to 4:30am in adults (Fischer et al 2017; Hashizaki et al 2015; Lucassen et al 2013; Rutters et al 2014). Our cohort’s sleep midpoints resemble those of morning chronotypes among obese adults (Lucassen et al 2013) and elderly individuals (Fischer et al 2017), which may speak to a morning preference in our older and obese cohort.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…We find a greater discordance to prior work with our cohort’s sleep midpoints, which typically vary from 3:00am to 4:30am in adults (Fischer et al 2017; Hashizaki et al 2015; Lucassen et al 2013; Rutters et al 2014). Our cohort’s sleep midpoints resemble those of morning chronotypes among obese adults (Lucassen et al 2013) and elderly individuals (Fischer et al 2017), which may speak to a morning preference in our older and obese cohort.…”
Section: Discussioncontrasting
confidence: 85%
“…Gender and race did not explain social sleep lag, which may reflect broader cultural norms and chronotype shifts in younger individuals regardless of background. The average weekend sleep duration of 8.59 hours closely matches sleep durations from other studies based on self-reported data (Fischer et al 2017; Koopman et al 2017; Liu et al 2012; Rutters et al 2014), which commonly overestimates sleep duration compared with objective measures such as actigraphy (Arora et al 2013; Dietch et al 2017; Lauderdale et al 2006; Silva et al 2007). Well-established trends in both objective and subjective sleep analyses demonstrate whites sleep upwards of 45 minutes longer than blacks (Dietch et al 2017; Lauderdale et al 2006), and women sleep upwards of 30 minutes longer than men (Dietch et al 2017; Lauderdale et al 2006; Liu et al 2012; Urbanek et al 2017), which are all consistent with our findings.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Inter-subject variability in circadian phase has been suggested, based on chronotype questionnaires administered to large populations of presumably healthy subjects [15]. Inter-subject differences in both daily timing and 24-h pattern have also been shown in individual patients collecting up to 5 daily samples of salivary cortisol and/or melatonin determinations for up to 2 days [16][17][18].…”
Section: Introductionmentioning
confidence: 99%